Life is beautiful = la vita e bella [videorecording]. (Pasig City : Viva Video Inc, 2000)
It's 1939 in Italy and Guido Orefice (Roberto Benigni) is a happy -go-lucky guy who's traveling with his brother. Arriving in Arezzo, Guido meets Dora (Nicoletta Braschi), a young and pretty school teacher. Imeediately smitten, Guido gets a job as a waiter and arranges to have more encounters with Dora. But it turns out that she's already engaged, albeit unhappily, to a Fascist official. But his charm wins over and they ride together for a life of happiness. The reality of war strikes several years later when Guido, who's Jewish, and their young son, Giosue (Giogio Catarini), are sent to a concentration camp. Fearing for her husband and son, Dora, who is not a jew, demands that she be allowed to go with them. Hoping to shield Giosue from the horrors of their predicament. Guido tells his son that they and everyone else in the camp are competing to win a contest where the grand prize is one of Giosue's favorite things - a real tank.